Tick-borne encephalitis in Slovenia (1953-2013): the 60th anniversary - Slavec Zvonka Zupanič; Medvešček Alenka Radšel; Slavec Ksenija (Sciendo, 2014)
Introduction: In the year 2013, we are celebrating the 60th anniversary of the isolation of the tick-borne encephalitis virus (TBE) in Slovenia. Ever since its isolation, Slovenian infectologists, epidemiologists, virologists and other experts have been researching this disease.